Two male patients from an extended seven generation Turkish family diagnosed with Renpenning syndrome: identifying the causative mutation and review of the literature - Toraman, Bayram; Dinçer, Tuba; Budak, Gülden; Bilginer, Cilem; Kayserili, Hülya; Kalay, Ersan (The European Research Journal, 2022)
Intellectual disability (ID) is a lifelong condition that begins during the developmental period, and characterized by significant limitations in intellectual functioning and adaptive behavior including social, conceptual and practical skills. In these case series, we aimed to identify the genetic etiopathogenesis of two male patients with ID from a seven-generation large-Turkish family. Two affected boys with syndromic ID were evaluated. Genome-wide auto zygosity mapping was performed on affected individuals and other available healthy family members for identifying shared chromosomal segments between affected individuals. Critical region co-segregating with the disease was confirmed and narrowed down by short tandem repeat polymorphism markers. Whole exome sequencing was performed to identify the responsible genes and mutations. Sanger sequencing was performed for segregation analysis. We performed a comprehensive genetic analysis to reveal the underlying genetic aetiology of the patients and identified a mutation on PQBP1 gene (NM_005710.2:c.459-462delAGAG) that is associated with Renpenning syndrome. Considering the clinical findings and genetic data of the affected probands, the patients were diagnosed with Renpenning syndrome and this is the first report for Renpenning syndrome with attention deficit and hyperactivity disorder comorbidity.